2021
DOI: 10.1212/wnl.0000000000011269
|View full text |Cite|
|
Sign up to set email alerts
|

Pathologic Features of Anti-Mi-2 Dermatomyositis

Abstract: ObjectiveTo identify the characteristic pathologic features of dermatomyositis (DM) associated with anti-Mi-2 autoantibodies (anti-Mi-2 DM).MethodsWe reviewed 188 muscle biopsies from patients (1) pathologically diagnosed with DM through the sarcoplasmic expression for the myxovirus-resistant protein A and (2) serologically positive for 1 of 5 DM-specific autoantibodies (DMSAs) (anti-Mi-2, n = 30; other DMSAs, n = 152) or negative for all 5 DMSAs (n = 6). We then compared the histopathologic and immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 47 publications
1
64
0
1
Order By: Relevance
“…The CFR value in all adult DM (0.7±0.3) was lower than the value in 12 normal adult muscle biopsy (1.1±0.1, P <.001). 11 The CFR did not significantly differ among DMSA subtypes (Figure 2C,D). Anti-Mi-2 DM were more commonly associated with increased ALP activity in the perimysium (70.0% vs. non-Mi-2 29.5%, P <.001).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…The CFR value in all adult DM (0.7±0.3) was lower than the value in 12 normal adult muscle biopsy (1.1±0.1, P <.001). 11 The CFR did not significantly differ among DMSA subtypes (Figure 2C,D). Anti-Mi-2 DM were more commonly associated with increased ALP activity in the perimysium (70.0% vs. non-Mi-2 29.5%, P <.001).…”
Section: Resultsmentioning
confidence: 86%
“…Histological features in anti-Mi-2 DM were compatible with those previously described in immune myopathy with perimysial pathology (IMPP). 11,18 By comparing each DMSA with other subtypes, anti-Mi-2 was significantly associated with PFA, 11,13 PFN, 11,18 PM-ALP, 11,18 inflammatory features, 11-13 perifascicular MxA expression, and sarcolemmal MAC expression. 11,13,18 We confirmed that anti-TIF1-γ DM was significantly associated with vacuolated fibers, 8 HLA-ABC expression with perifascicular enhancement and distinctive capillary MAC deposition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations